Influence of duration and visual feedback on the perception of tactile illusions of motion. - Remache-Vinueza, Byron; Guijarro Molina, Irene; Trujillo-León, Andrés (Springer Nature, 2025)
Tactile illusions manifest when the perceived sensation does not align with the actual tactile stimulation. Phantom motion and cutaneous rabbit are two illusions that convey motion and direction information using only a pair of actuators, which results in reduced cost, weight, and energy consumption. This study presents two experiments involving these illusions. In the first of them, participants grasped a two-actuator haptic interface. It explored how the duration of the illusions influences the distance traveled by the illusory points. For phantom motion, duration directly affects the perceived end-point location. As duration increases, the end-point starts being sensed out of the hand, either in the interface or even in the air. On the other hand, cutaneous rabbit illusion is not influenced by duration. The second experiment investigated the influence of visual feedback on the perception of both tactile illusions. Visual stimuli were presented paired with their haptic counterpart. Results show a clear dominance of vision over the haptic mode in both phantom motion and cutaneous rabbit illusions. Characteristics such as the motion location, direction, distance traveled, or number of jumps in cutaneous rabbit were fixed by the visual stimulus, no matter the content of the haptic cue. This finding opens a world of possibilities for integrating tactile illusions in visuo-haptic experiences typical of Virtual Reality environments: simple setups with two actuators are enough to elicit clear and varied haptic perceptions when presented together with the appropriate visual stimulus.
Keywords: Dispositivos hápticos; Percepción táctil; Haptic illusion; Tactile illusion; visual feedback; Tactile feedback; Duration